Community in Conflict : A Working-class History of the 1913-14 Michigan Copper Strike and the Italian Hall Tragedy - Kaunonen, Gary; Goings, Aaron (Book collections on Project MUSE., 2013)
"A mirror of great changes that were occurring on the national labor rights scene, the 1913-14 Michigan Copper Strike was a time of unprecedented social upheaval in Michigan's Upper Peninsula. With organized labor taking an aggressive stance against the excesses of unfettered capitalism, the stage was set for a major struggle between labor and management. The Michigan Copper Strike received national attention and garnered the support of luminaries in organized labor like Mother Jones, John Mitchell, Clarence Darrow, and Charles Moyer. The hope of victory was overshadowed, however, by violent incidents like the shooting of striking workers and their family members, and the bitterness of a community divided. No other event came to symbolize or memorialize the strike more than the Italian Hall tragedy, in which dozens of workers and working-class children died. In Community in Conflict, the efforts of working people to gain a voice on the job and in their community through their unions, and the efforts of employers to crush those unions, take center stage. Previously untapped historical sources such as labor spy reports, union newspapers, coded messages, and artifacts shine new light on this epic, and ultimately tragic, period in American labor history."--Publisher's website